2016
DOI: 10.1515/euco-2016-0009
|View full text |Cite
|
Sign up to set email alerts
|

Regional Food Preference and Awareness of Regional Labels in Vysočina Region (Czech Republic)

Abstract: The article presents results of research on preference of the regional food in Vysočina Region in the Czech Republic, with main focus on awareness analysis of Vysočina regional labels. Presented findings are a part of longitudinal research that aims to analyse the evolution of Czech regional labels and their impact on regional development. The questionnaire survey was conducted between January and March 2015 on the sample of 819 respondents from the Vysočina Region. The data have been processed with correspond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 15 publications
1
24
0
Order By: Relevance
“…Hidalgo-Baz et al (2017) deal with the issue of food quality, since its definition remains unclear when it comes to organic products. A study carried out by Chalupová et al (2016) offers findings resulting from a regional food preference analysis in the Vysočina region, Czech Republic, with main focus on awareness analysis of Vysočina region labels. In line with the aforementioned study, our research too posed a question assessing respondents' familiarity with the labelling of organic food.…”
Section: Introductionmentioning
confidence: 99%
“…Hidalgo-Baz et al (2017) deal with the issue of food quality, since its definition remains unclear when it comes to organic products. A study carried out by Chalupová et al (2016) offers findings resulting from a regional food preference analysis in the Vysočina region, Czech Republic, with main focus on awareness analysis of Vysočina region labels. In line with the aforementioned study, our research too posed a question assessing respondents' familiarity with the labelling of organic food.…”
Section: Introductionmentioning
confidence: 99%
“…From the marketing perspective, it is important to understand who buys regional food and why is valuable for targeting efforts by producers, retailers, shop owners, restaurants, and others needing information on consumer demand for regional food. Previous analysis (Chalupová, Rojík, Prokop, 2016) confirmed that the preference of regional food in Vysočina Region is strongly depends on the residence in Vysočina Region districts, the lowest preference of the Vysočina regional food is in Žďár nad Sázavou district, respondents living in this district being significantly different in their preferences from the others. The authors are aware of the limitations of the research, as it would be important to know opinions of the Vysočina Region visitors, as the regional labels also aim at them, test awareness and attitudes towards this labelled production on other regional markets to identify possible business potential.…”
Section: Resultsmentioning
confidence: 70%
“…In comparison with surveys of other authors who analysed the awareness of regional brands in their research, the result may be viewed as positive. Chalupová, Prokop and Rojík (2016), who examined the brand VYSOČINA regional product, recorded the awareness of the brand only by 31 % of respondents. Awareness of regional brands correlates with respondents' age, education and also status toward the region.…”
Section: Discussionmentioning
confidence: 99%